A high-level Petri net based model for web services composition and verification. (2015) - Chemaa, Sofiane; Bouarioua, Mouna; Chaoui, Allaoua
The evolution of the internet and the competitiveness between enterprises are the major factors in the explosion of web services use. The concept of web services composition is a natural evolution of this technology. It aims to build new value added services, using existing ones. However, this task remains highly complex and requires formal techniques for its completion. In this paper, we propose a high level Petri nets approach that successfully accomplishes this task. In this context, we define a web service modelling technique using the G-net formalism. We also propose an expressive algebra that permits the combination of the modelled services. In order to take benefit from the Maude formal verification tools, we have suggested a method that permits the translation of a modelled service from a G-net model to an equivalent Maude specification. The defined approach has successfully been automated using the Java programming language.